Corporate Social Responsibility of Family Firms : The Effect of Institutional Context and Board of Directors - Paulis, Domingu Vithanage Hiruda Nilupul (2017)
Corporate Social Responsibility (CSR) is an important phenomena to organisations since, sustainable performance, long term survival and increased value and reputation of both firm and owners. The main objectives of this study was to understand what board characteristics have an effect on CSR performance of family firms and to understand how a family firm being located in an emerging economic context moderates the influence of director board on overall CSR performance of a family firm. In addition, contributing to both empirical and theoretical knowledge on relatively understudied, influence on CSR performance by foreign directors. In order to fulfil the objectives, a sample of 201 public companies were selected from both emerging and non-emerging economies. Content analysis of annual reports of publicly held family firms was used as a tool to collect majority of data while online commercial databases were used to extract data for few variables. Collected sample was first subjected to multiple linear regressions and then moderator variables were subjected to hierarchical linear regression to derive moderating effect of emerging economies. Direct relationship between overall CSR performance of family firm and both director board characteristics and presence in emerging economic context was observed as insignificant. However, it was further evident that both independent directors and female directors have significant positive and negative effect respectively on CSR performance when moderation effect of emerging economic context is considered.